Kesadaran Halal dalam Pengambilan Keputusan Konsumsi Makanan oleh Mahasiswa FEBI UIN Ponorogo - Shelvi Ardita Dela Putri; Mun Yah Zahiroh (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: Halal awareness has become an important issue among Muslim consumers, particularly among university students who are expected to possess adequate knowledge regarding Islamic consumption principles. However, there is often a gap between understanding the importance of halal food and its implementation in daily consumption behavior. This study aims to analyze halal awareness among students of the Faculty of Economics and Islamic Business (FEBI), UIN Ponorogo, and examine its influence on food consumption decision-making. Research Methods: This research employed a descriptive qualitative approach with a field research design. Results: The findings indicate that students generally possess a good understanding of halal concepts, including knowledge of halal products, religiosity, and perceptions regarding cleanliness and safety. Conclusion: Halal awareness affects several stages of consumer decision-making, particularly information searching, product evaluation, purchase decisions.